Comparing the effectiveness of cognitive- behavioral hypnotherapy and mindfulness therapy on pain perception and self-efficacy in women with breast cancer in Gorgan - Yusefi, Rahman; Hafezi, Fariba; Bakhtiarpoor, Saeed; Makvandi, Behnam (Applied Family Therapy Journal (AFTJ), 2022)
Aim: Without a doubt, breast cancer is one of the most stressful events for women, and patients usually experience a severe shock when faced with a cancer diagnosis. The present study was conducted with the aim of comparing the effectiveness of cognitive-behavioral hypnosis-based therapy and mindfulness-based therapy on pain perception and pain self-efficacy in women with breast cancer. Methods: The design of the research was semi-experimental and pre-test-post-test and follow-up with the control group. The statistical population of the present study was all women with breast cancer who referred to Mirdamad Radiotherapy and Oncology Center in Gorgan city in the second half of 2018. For this purpose, 45 people were selected and randomly divided into three groups. In the first test group, Donald Robertson's (2012) cognitive-behavioral hypnotherapy treatment protocol was used. In the second experimental group, mindfulness-based therapy sessions were conducted based on the mindfulness-based therapy guide of Segal et al. (2002) during 8 sessions. The control group did not receive any intervention. The research tools included Nicholas Pain Self-Efficacy Scale (1998) and McGill Pain Perception Questionnaire (1997). The research data were analyzed using the analysis of variance test with repeated measurements. Results: The results of data analysis showed that compared to the control group, both treatment methods had a significant effect on pain perception (F=55.19, P